Time to diagnosis and determinants of diagnostic delays of people living with a rare disease: results of a Rare Barometer retrospective patient survey - Faye, Fatoumata; Crocione, Claudia; Anido de Peña, Roberta; Bellagambi, Simona; Escati Peñaloza, Luciana; Hunter, Amy; Jensen, Lene; Oosterwijk, Cor; Schoeters, Eva; de Vicente, Daniel; Faivre, Laurence; Wilbur, Michael; et al. (European journal of human genetics : EJHG, 2024)
Timely diagnosis is one of the most serious challenges faced by people living with a rare disease (PLWRD), and this study estimates that in Europe, the average total diagnosis time (TDT) is close to 5 years. We investigated the duration of the TDT for PLWRD in Europe, the difficulties associated with their diagnosis odyssey and the main determinants of diagnosis delays for all rare diseases (RD). We conducted a survey of PLWRD and their families using Rare Barometer, the survey initiative of EURORDIS-Rare Diseases Europe. In geographical Europe, we surveyed 6507 people living with 1675 RD in 41 countries. We then performed a descriptive analysis and ordinal logistic regressions to identify the main determinants of diagnosis delays. Average TDT is 4.7 years. 56% of respondents were diagnosed more than 6 months after a first medical contact. The main determinants of diagnosis delays are symptom onset before 30 years of age, especially during childhood (OR = 3.11; 95% CI: 2.4-4.0) and adolescence (OR = 4.79; 95% CI: 3.7-6.2), being a woman (OR = 1.22; 95% CI:1.1-1.4), living in Northern Europe (OR = 2.15; 95% CI:1.8-2.6) or Western Europe (OR = 1.96; 95% CI:1.6-2.3), the number of healthcare professionals consulted (OR = 5.15; 95% CI:4.1-6.4), misdiagnosis (OR = 2.48; 95% CI:2.1-2.9), referral to a centre of expertise (OR = 1.17; 95% CI:1.0-1.3), unmet needs for psychological support (OR = 1.34; 95% CI:1.2-1.5) and financial support (OR = 1.16; 95% CI:1.0-1.3), having a genetic disease (OR = 1.33; 95% CI:1.1-1.5) and a family history of an RD (OR = 1.36; 95% CI:1.1-1.6). These determinants can inform policies and actions to improve access to diagnosis for all PLWRD.